Amputation side and site determine performance capacity in Paralympic curve sprinting - Funken, J.; Heinrich, K.; Willwacher, S.; Müller, R.; Potthast, W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
In the 2015 IPC world championships athletes with amputation at the inside leg were underrepresented in the finals of the 200 and 400 m sprinting events. Yet there is only very limited information on amputee curve sprinting and the influence of side and/or level of amputation on propulsion mechanisms. The aim of this study was to describe amputee curve sprinting kinetics and to it compare to able-bodied athletes. Three amputee athletes with different amputations of the lower limb and six able-bodied athletes performed curved runs. Results show differences between athletes in the ability to create high vertical and centripetal forces and suggest a dependence on site (above and below knee) and side (left or right) of amputation. Running specific prosthesis might benefit from design adaptation if used at the left limb in curve running.